2016
DOI: 10.1016/j.stemcr.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Stimulation and Laminins Support Cardiovascular Cell Progenitor Expansion from Human Fetal Cardiac Mesenchymal Stromal Cells

Abstract: SummaryThe intrinsic regenerative capacity of human fetal cardiac mesenchymal stromal cells (MSCs) has not been fully characterized. Here we demonstrate that we can expand cells with characteristics of cardiovascular progenitor cells from the MSC population of human fetal hearts. Cells cultured on cardiac muscle laminin (LN)-based substrata in combination with stimulation of the canonical Wnt/β-catenin pathway showed increased gene expression of ISL1, OCT4, KDR, and NKX2.5. The majority of cells stained positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…Mumtaz, et al showed that ZIKV infection perturbs osteoblast-derived MSC function without causing cytopathic effects, and additionally found a delay in osteoblast development and maturation compared to uninfected controls [25]. To determine whether ZIKV can infect and replicate in cells relevant to cardiac pathophysiology, we utilized fetal cardiac mesenchymal stromal cells (fcMSCs), which were previously isolated from fetal hearts of six to nine-weekold embryos [26]. Cardiac MSCs represent a major population of non-myocyte heart cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mumtaz, et al showed that ZIKV infection perturbs osteoblast-derived MSC function without causing cytopathic effects, and additionally found a delay in osteoblast development and maturation compared to uninfected controls [25]. To determine whether ZIKV can infect and replicate in cells relevant to cardiac pathophysiology, we utilized fetal cardiac mesenchymal stromal cells (fcMSCs), which were previously isolated from fetal hearts of six to nine-weekold embryos [26]. Cardiac MSCs represent a major population of non-myocyte heart cells.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation in our study is that we did not compare the survival of cartilage implants with and without Geltrex. In the future, it will be necessary to evaluate the effect of Adv-RFP-LOXL2 in implants without Geltrex to determine if its benefits are related to its ability to promote pluripotent stem cell differentiation and support chondrogenesis 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These implants were surgically implanted subcutaneously in the backs of nude mice (3 implants/mouse). These explants were implanted with specialized matrix (Geltrex; ThermoFisher Scientific, Inc) as a basement membrane to promote a chondrogenic environment 21 , 22 . Geltre matrix is composed of laminin, collagen IV, entactin, and heparan sulfate proteoglycans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations